Preservasi Sejarah: Eksplorasi Warisan Kesultanan Serdang di Kabupaten Serdang Bedagai - Prayogo, Agung; Harahap, Indra; Nasution, Raihani Dewi; Astaman, Raden Bagus (Lembaga Yasin AlSys, 2024)
This paper aims to explore the heritage of the Serdang Sultanate in Serdang Bedagai Regency, there are Serdang Sultanate sites that still exist and are maintained as a preservation effort that is widely recognized and preserved. The type of research used is qualitative with a historical approach, primary data is collected through literature study, observation and documentation of existing historical sites, secondary data completes studies related to themes related to the title through published scientific writing sources; books, theses and journal articles as support for this research. The findings explain the importance of understanding and maintaining the history of the Serdang Sultanate as an integral part of cultural heritage. The construction of a replica of the Darul Arif Palace is concrete evidence of care and determination to maintain authenticity and revive the history of the Serdang Sultanate. The renovation of the Sulaimaniyah Mosque shows a commitment to maintaining the continuity of the main function of the mosque as a center of worship and a silent witness to the development of the Serdang Sultanate. The maintenance of the tombs of sultans reflects a deep appreciation for historical figures.